2016
DOI: 10.1038/nmat4576
|View full text |Cite
|
Sign up to set email alerts
|

Charge transport and localization in atomically coherent quantum dot solids

Abstract: Epitaxial attachment of quantum dots into ordered superlattices enables the synthesis of quasi-two-dimensional materials that theoretically exhibit features such as Dirac cones and topological states, and have major potential for unprecedented optoelectronic devices. Initial studies found that disorder in these structures causes localization of electrons within a few lattice constants, and highlight the critical need for precise structural characterization and systematic assessment of the effects of disorder o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
402
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(423 citation statements)
references
References 36 publications
20
402
1
Order By: Relevance
“…[17][18][19][20][21][22][23] The inherent large surface-to-volume ratio of QD materials results in unsaturated dangling bonds, creating undesired electronic trap states within the bandgap of QD solids. The ligand exchange procedure itself is prone to create new, rather than passivate existing, dangling bonds.…”
mentioning
confidence: 99%
“…[17][18][19][20][21][22][23] The inherent large surface-to-volume ratio of QD materials results in unsaturated dangling bonds, creating undesired electronic trap states within the bandgap of QD solids. The ligand exchange procedure itself is prone to create new, rather than passivate existing, dangling bonds.…”
mentioning
confidence: 99%
“…In the n-channel operation, the drain current remarkably increases with the temperature, indicating that electron transport in PbSe NR assemblies is thermally activated (hopping transport). [33] Negligible hysteresis is observed between forward and reverse scan in the n-channel transfer characteristics at temperatures between 240 and 60 K, while a distinct hysteresis appears above 240 K and a small hysteresis is reappearing below 60 K (Figure 4 and Figure S7, Supporting Information). In the p-channel operation, the drain current also increases with increasing temperature with some fluctuation, but the large hysteretic behavior remains over the whole temperature range showing a decrease at low temperature.…”
Section: Resultsmentioning
confidence: 99%
“…[27] Moreover, the presence of trap states, which may stem from (i) the synthetic process; (ii) the ligand-exchange during fabrication; (iii) adsorption of molecules (e.g., water and oxygen) at the interface between the active layer and gate dielectric, [28] is responsible for not ideal transport properties. Again, while a large number of papers discuss results on PbS and PbSe spherical QDs, [12,[29][30][31][32][33] very little is known on PbSe rods charge transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Whitham et al . [151] demonstrated that charge localization can be greatly suppressed by reducing the level of disorder in CQD films, by epitaxially connecting ordered PbSe nanocrystals.…”
Section: Quantum Dots For Photovoltaic Applicationmentioning
confidence: 99%